Law and Consumer Protection - Muhammad Anas Arifin; Kelik Wardiono (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
This research aims to describe forms of unfair business competition practices that result in scarcity of 3kg LPG Gas and consumer protection, is based on legal research with a non-doctrinal approach. The data in this study are primary data collected through interviews with purposively selected informants, as well as supported secondary data collected by literature study. Based on the results of research and discussion conducted on business actors, it was found that there were business actors engaging in unfair business competition by practicing closed agreements; as well as business actors who carry out monopolistic practices, resulting in scarcity of 3 Kg LPG Gas and harming consumers.